CHILDREN EDUCATION IN THE ISLAMIC FAMILY A Study Of Tuhfah Al Maudud Bi Ahkam Al MauludBy Ibn Qayyim Al Jauziyyah - Muhammad Idris; Abd. Mukti (State Islamic University of North Sumatra Indonesia, 2017)
This study aimed to reveal how IbnQayyim al-Jawziyyah thought about the education of children in Islamic families as in his paper Tuhfah al Maudud bi Ahkam al Maulud. There are three problem formulations proposed in this study: first, how the intellectual social conditions of writing the book Tuhfah al Maudud bi Ahkam al Maulud; Second, how is the thinking about the education of children in the Islamic family contained in the book of Tuhfah al-Maudud bi Ahkam al-Maulud; Third, how relevant the idea is to contemporary Islamic education. This research is library research; And using a social history approach; The steps are taken: first, collecting reference works, grouped into two: primary and secondary sources (other sources in the same theme are used as a complement); Second, using content analysis methods, with the steps: first, reading the text and giving a brief note on the margin when it finds the required information; Second, categorize and identify each item according to a cognate theme; Third, comparing all categories, both major and minor; Fourth, after all data is categorized into categories large and small, review, to ensure that the information is categorized as appropriate; Fifth, re-examine the original text, and ensure that all the information that needs to be categorized has all been listed; Sixth, material analysis, interpretation, and meaning. Furthermore, Ibn al-Qayyim's ideas on child education are analyzed by taking into account the potential relevance for today's education. The findings of this study: first, where during Ibn al-Qayyim's lifetime, the political, social, and educational conditions were in an unstable state. Second: education for children in Ibn al-Qayyim's thinking as stated in his paper Tuhfah al-Maudud bi Ahkam al Maulud consists of: moral education for children; Aqidah education for children; And education of worship for children. Third: education for children according to Ibn al-Qayyim's thought is still relevant, evidenced by the similarity of discussion and practice of education in today's world.